Lapan-Lapan Express: Innovating Traditional Lalapan into a Modern Fast-Food Concept - Wiryawan, Balqis Srikandi; Handrito , Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to develop a business plan for Lalapan “Lapan-Lapan” by designing a new business concept, Lalapan Lapan-Lapan Express, to overcome challenges related to product differentiation and operational design while supporting business growth in Malang City. Design/Methodology/Approach – This study employs a qualitative descriptive research approach. Data were collected through observations and document studies. The business feasibility analysis was conducted by evaluating five key aspects: product, marketing, operations, organization and management, and finance. The analysis was used to formulate strategic development plans and assess the feasibility of establishing fast-food takeaway outlets with Lalapan Bowl as the main product differentiation. Findings – The results indicate that the establishment of Lalapan Lapan-Lapan Express is feasible and has strong growth potential. The proposed business concept provides product differentiation through Lalapan Bowl while addressing existing challenges in product uniqueness and operational effectiveness. The business plan demonstrates promising financial projections, significant profit potential, and relatively low business risks, indicating opportunities for sustainable expansion in the culinary market. Originality/Value This research is original in proposing a fast-food takeaway concept, “Lalapan Lapan-Lapan Express,” as a strategic solution for a local culinary business. The findings provide practical value by offering a comprehensive business plan covering product, marketing, operations, organization, and finance to support rapid growth and profitability.